The effects of melatonin and metformin on histological characteristics of the ovary and uterus in letrozole-induced polycystic ovarian syndrome mice: A stereological study - Parvin Lohrasbi; Saied Karbalay-Doust; Seyed Mohammad Bagher Tabei; Negar Azarpira; Sanaz Alaee; Bahare Rafiee; Soghra Bahmanpour (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Polycystic ovarian syndrome (PCOS) with anovulation, hyperandrogenism, ovarian and uterine histological changes, menstrual irregularities, etc. signs is an infertility type. It seems that melatonin and metformin can improve these abnormalities. Objective: To evaluate the effects of melatonin and metformin on the ovary and uterus in PCOS-induced mice using stereological methods. Materials and Methods: Seventy-two adult female BALB/c mice (8-wk-old, 20-30 gr) were randomly divided into control (distilled water, gavage), PCOS (90 µg/kg letrozole, gavage), PCOS+metformin (500 mg/kg, gavage), PCOS+melatonin (10 mg/kg, intraperitoneal injection), and PCOS+melatonin control (0.5% ethanol saline) groups (n = 12/each). Another PCOS group was kept for a month to ensure that PCOS features remained. Finally, a stereological evaluation of the uterus and ovary was carried out, and vaginal cytology and serum testosterone levels were assessed. Results: PCOS mice treated with metformin and melatonin had lower testosterone levels, body weight, and more regular estrus cycles than the PCOS group (p ≤ 0.001). A significant decrease in conglomerate and daughter gland numbers, and primary, secondary, atretic, and cystic follicles numbers with a significant increase in primordial and Graafian follicles, and corpus luteum numbers (p ≤ 0.001) was seen in these treated mice. Also, endometrial vessels' volume and length significantly increased, but ovarian, endometrial, myometrial, stromal, and glands volume, and endometrial and myometrial thickness dramatically declined (p ≤ 0.001). Conclusion: It appears that metformin and melatonin could restore the PCOS phenotype including estrus cycle irregularity, high testosterone level, and ovarian and uterine micromorphology to the control levels. However, the 2 treatments had similar effects on the examined parameters.